DOES PRESENCE OF CL AND/OR FOLLICLE ON THE OVARY INFLUENCE THE SUBSEQUENT FOLLICULAR DYNAMICS IN TWO- AND THREE-WAVE CYCLES OF CATTLE? - Hadiya, KK; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
This investigation was undertaken on 24 unbred cyclic Gir and HF x K crossbred cattle of University farm for one cycle to see the influence of presence of CL and/or follicle on the subsequent development of dominant and ovulatory follicles in two- and three-follicular wave cycles using 7.5 MHz real time B-mode transrectal ultrasound scanning. The development of the first, second and third dominant follicle, and ovulatory follicle in relation to the position (ipsi- or contra-lateral) of the CL and the presence of morphologically dominant follicle were evaluated in both Gir and crossbred cattle, irrespective of parity. In both Gir and crossbred animals with 2-wave cycles, there was no relationship between the development of first dominant follicle and presence of CL in either of the ovaries, while in 3-wave cycle the first dominant follicle and the ovulatory follicle developed contralateral to the ovary bearing the CL, while the second dominant follicle developed on the same ovary bearing the CL. Similarly, no pattern was observed for the development of ovulatory follicle with respect to first dominant follicle on the ovaries in 2-wave cycle. However, the proportion of ovulatory follicles was higher on opposite side as compared to same side to the first dominant follicle in 2-wave cycle in both the breeds. In 3-wave cycle the second dominant follicle developed contralateral to first dominant follicle and the ovulatory follicle developed contralateral to second dominant follicle in all the animals. Thus, there was no difference in the pattern of this phenomenon between two breeds studied. In both Gir and Crossbred cows, the average CL size and plasma P4 values were significantly higher (P < 0.01) while follicle size and plasma E2 values were lower on day 7 and 14 than on day 0 and 21 post-estrus. Moreover, there were positive correlations between CL diameter and plasma P4 values (r = 0.82 and 0.72), and follicle size and E2 values (r = 0.69, 0.36) in two breeds studied.
Keywords: Follicle size; CL size; Follicular dynamics; Cattle; Plasma Steroid profile